PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VA SD NEGERI 038 SEKELADI HILIR - Efriatul Antoni; Eddy Noviana; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Absract: The problem this research is the students achievement of sains studies SD Negeri 038 Sekeladi Hiliramatan Tanah Putih fourth graderes still low with an average value of 60,5 and minimum completeness criteria (KKM) sains studies is 70. Between students, amounting to 20 people only 7 students who achieve classical KKM with 35 %. This research is Classroom Action Research (CAR), which aims to improve the student achievement of sains studies class VA at SD Negeri 038 Sekeladi Hilir with implementation approach CTL. Formulation of the problem : Is the implementation of approach CTL can improve students achievement of sains studies at SD Negeri 038 Sekeladi Hilir. The research was conducted on April 27, 2017 to Mei 15, 2017 by 2 cycles. Subjects were students of SD Negeri 038 Sekeladi Hilir, totaling 20 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 60,5. in the first cycle improve an average 72 and an improve in the second with an average of 81,25. Activities of the teacher in the learning process in cycle of 58,33% and the second meeting improve 77,77%. Cycle II first meeting and the second meeting improve 80,55% and the second meeting improve 91,66%. Results of data analysis of students activities in the first cycle with the first meeting of an average 55,55% and a second meeting improve to 75,0% . Cycle II first meeting improve 77,77% and the second meeting improve to 89%. Resultsin the class VA at SD Negeri 023 Sedinginan Kecamatan Tanah Putih that the implementation of approach CTL can improve student achievement of sains studies at fourth graderes SD Negeri 038 Sekeladi Hilir.Key Words+: Approach, Contextual Teaching and Learning (CTL), Students Achievement, Sains.